A learning process of a child with visual impairment in regular classroom : a case study - Siti Maisara Unaizah, Mustafa (Universiti Malaysia Sarawak (UNIMAS), 2009)
The purpose of this study is to examine the effectiveness of regular classroom towards the learning process of a child with visual impairment. The respondents were three students with visual impairment in an integrated school in Kuching. They were observed during the teaching and learning process and interviewed, and their work samples were taken as part of data regarding their learning process in regular classroom. The data were analyzed using qualitative analysis such as transcribing interview data, synthesizing and emerging critical themes. Three main theme such as critical thinking, creative thinking and complex thinking towards the learning process in regular classroom were discussed The finding shows that, in general, four categories were derived in the learning process of the students with visual impairment in regular classroom for critical thinking which are recall, recognition, encoding specificity and forgetting. The finding also shows that creative thinking of students with visual impairment involved three categories such as synthesizing, imagining and elaboration of information. The findings of the study show that students with visual impairment in regular classroom were able to perform the complex thinking by performing problem solving.